Altitudinal gradient drives significant changes in soil physico-chemical and eco-physiological properties of Rhododendron anthopogon: a case study from Himalaya - Mangral, Zahid Ahmed; Islam, Shahid Ul; Tariq, Lubna; Kaur, Sharanjeet; Ahmad, Rameez; Malik, Akhtar H.; Goel, Shailendra; Baishya, Ratul; Barik, Saroj Kanta; Dar, Tanvir Ul Hassan (Frontiers in Forests and Global Change, 2023)
The best natural laboratories for studying the ecological responses of plants are high-altitude areas like the Himalaya, where many gradients coexist on a relatively small spatial scale. Here, we investigate the effect of soil physico-chemical and eco-physiological properties on the broadleaf evergreen woody shrub Rhododendron anthopogon D.Don along an altitudinal gradient in the Kashmir Himalaya. We collected leaf and soil samples for eco-physiological and soil physico-chemical analysis, respectively, at five different sites along an altitudinal gradient (3,220–3,908 m). Our results demonstrate a significant difference between soil physico-chemical and eco-physiological parameters along the altitudinal gradient. A significant correlation was observed between different studied parameters and altitude. Principal component analysis of studied soil physico-chemical and eco-physiological parameters revealed that all the sites were grouped into four clusters according to altitude, suggesting a more pronounced effect of altitude. Our findings showed that soil infiltration capacity increased with altitude, which would be helpful for the growth and development of R. anthopogon. We also observed significant variations in eco-physiological parameters, demonstrating their critical involvement in adapting R. anthopogon to the harsh environment of the alpine regions of Kashmir Himalaya. Therefore, the present study adds to our understanding that R. anthopogon has sufficient soil physico-chemical and eco-physiological plasticity, which should be favorable for its survival in future climates, offering an adaptive advantage and expanding its range shortly.